THE MANIFESTATION OF CRITICAL THINKING ELEMENTS IN EFL STUDENTS’ ARGUMENTATIVE WRITING - Halum, Yustus Sentus; Guna, Stanislaus (TELL - US JOURNAL, 2021)
This qualitative study aims at investigating patterns of argumentative structure manifested in the students’ argumentative paragraphs. The result of this study showed that the six elements of critical thinking proposed by Stapleton were represented in the students’ argumentative writing. Arguments were used by all the 30 students (100%), reasons were 21 students (70%), evidences were 20students (66,7%), refuse of opposition (ROP) were 10 students (33,3%), conclusion were 15 students (50%), and then fallacies were used by 25 students (83,3%). Based on the result of this study it can be concluded that all the critical thinking elements proposed by Stapleton were manifested in the third grade students’ argumentative writing.  However, not all the students put all the six elements in their writing except argument. Most of the students overwhelmed in highlighted the refutation point of view in whole their argumentative essay and then in drawing the conclusion.  Indeed, most of students produced many fallacies which made their argument weak. Based on the numbers of students who put those elements, the total of each criteria existence also counted. The dominant presence of those criteria were fallacies, which impacted by the lack of putting logical reasons, evidences and illogical conclusion as could be the effect of students’ reading habit. The weakest numbers of ROP indicated the students made the readers difficult to decide whether pro or contra to their standing positions.